Occupational safety and health risks of farmers: A qualitative study in Guyana. - Parasram, Barry; Choudhury, Avishek (Work, 2025)
Background: Despite extensive evidence highlighting the detrimental effects of pesticide exposure on farmers in Low and Middle Income Countires (LMICs), the issue remains unresolved. A research gap persists in understanding why well-documented hazards and existing interventions—ranging from safety training programs to policy reforms—have not translated into widespread improvements in farmer safety. Objectives: The present study aims to understand the perception of farmers and the ministry of agriculture in Guyana regarding pesticide use, safety practices, regulatory enforcement and strategies for improving occupational health outcomes. Methods: A qualitative phenomenological approach was used to capture the in depth perspectives of 16 agricultural extension officers from the National Agricultural Research and Extension Institute and 16 farmers across the various agricultural sectors using semi-structured 30-min-long interviews. Results: Responses revealed seven themes: (a) Barriers to Proper Use of Personal Protective Equipment (PPE), (b) Challenges in Safe Chemical Use, (c) Health Impacts of Unsafe Chemical Exposure, (d) Challenges in Farmer Training and Adoption of Safety Practices, (e) Lack of Policies and Monitoring for Farmer Safety and Chemical Use, (f) Absence of Quality Control and Unsafe Practices in Local Produce, and (g) Lack of physical safety and insurance. Each theme highlights differences in perceptions between farmers and Ministry of Agriculture officials, and is interpreted through structural, cultural, and behavioral lenses. Conclusion: Our study reveals a reinforcing relationship between systemic gaps, unsafe practices, and poor outcomes. Addressing these challenges requires a participatory approach that bridges the perceptual gaps between the agriculture ministry and farmers.